Metaphor and theory: a case study of astronomy - Tonci Grubic (Prometheus)
Metaphors enable the understanding of one thing in terms of another. Although central to reasoning and theorizing, there is limited understanding about their role in theory development. This paper presents a process of metaphorical reasoning that addresses the question of how metaphors support theory development. The process is applied to the case of astronomy, which helps explain why metaphors create reality and why their reality-creating side cannot be separated from their creative side. The paradoxical nature of metaphors means that metaphorical reasoning is an open-ended process. The paper also shows that emergence – a fundamental property of metaphors – explains their paradoxical nature. This same property makes metaphor a compressed interpretation of the world, characterized by the discarding of information. Finally, it is argued that metaphors are abstract intermediaries between senses and experiences. Given that metaphors are central to reasoning and theorizing, it is not surprising that these findings are consonant with what we know about theory (creative, reality-creating, sparse, abstract and open-ended). What is surprising, though, is that the discarding of information seems to be essential for the building of theory. The paper concludes by exploring what this entails for our understanding of theory.